Assessment of biofilm removal capacity of a broad host range bacteriophage JHP against Pseudomonas aeruginosa. Issue 6 (18th April 2017) - Shafique, Muafia; Alvi, Iqbal Ahmad; Abbas, Zaigham; ur Rehman, Shafiq
Abstract : Pseudomonas aeruginosa is an efficient biofilm‐dwelling microbial pathogen, associated with nosocomial infections. These biofilm‐associated infections are resistant to antibiotics and immune defenses, therefore pose major problem against their treatment. This scenario demands alternative therapeutic regimens, and bacteriophage therapy is one among potential strategies for clinical management of multiple drug resistance. In this investigation, the efficacy of a bacteriophage, JHP, is evaluated to eradicate P. aeruginosa biofilms. Growth kinetics of P. aeruginosa biofilm revealed that the highest cell density biofilm (1.5 × 10 16 CFU/mL) was established within the polystyrene microtiter plate at 72 h post inoculation. Pseudomonas aeruginosa biofilms of different ages, treated with JHP (0.6 MOI) for different post‐infection durations, reduced biomass from 2 to 4.5 logs (60–90%). JHP treatment before biofilm development reduced the bacterial load up to 9 logs (>95% bacterial load reduction) as compared with untreated control, which highlights its potential to prevent biofilm formation in indwelling medical devices. Combinations of JHP with other phages or antibiotics could be an efficient alternative for P. aeruginosa biofilm removal in clinical and industrial settings.